Preparation method of carbon nanotube coated functional titanium alloy composite powder
By performing high-temperature fluidization treatment and chemical vapor deposition technology in a fluidized bed reactor, titanium alloy composite powder with high spherical and uniform carbon nanotube distribution was prepared, solving traditional mechanical mixing The preparation of carbon nanotube-titanium composite powders has problems such as low spherical shape and poor fluidity, and has achieved the preparation of high-quality composite powders suitable for 3D printing.
Patent Information
- Application Number
- CN202311041645.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
The preparation of carbon nanotube-titanium composite powders by traditional mechanical mixing methods has problems such as low spherical shape, poor fluidity, damaged carbon nanotube structure and uneven distribution, which makes it impossible to be effectively used for 3D printing.
The fluidized bed reactor was used to prepare titanium alloy composite powder coated with carbon nanotubes. The oxide film on the surface of the titanium alloy powder was removed through high-temperature fluidization treatment and the internal catalyst was activated. The chemical vapor deposition technology was used to titanium alloy powder. Carbon nanotubes grow in situ on the body surface.
The prepared carbon nanotube clad functional titanium alloy composite powder has high spherical shape, good fluidity, low impurity content and uniform carbon nanotube distribution. It is suitable for 3D printing, and has a simple process, low cost and easy to produce on a large scale.
Smart Images

Figure CN119491201A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing of metal-based composite materials, and specifically relates to a 3D printing technology for preparing powder raw materials for titanium-based composite materials with high performance and special functions, and more specifically to a method for preparing carbon nanotube-coated functional titanium alloy composite powder. Background Art
[0002] Titanium alloy is an important engineering material, which is widely used in the fields of automobile, aerospace, biomedicine, etc. The alloy composition design can not only improve the mechanical properties, but also give titanium alloy special functions. For example, TiNi alloy with shape memory function, TiFe alloy with hydrogen storage function, and TiCo alloy widely used in the biomedical field. With the rapid development of key engineering fields such as aerospace, national defense science and technology, and deep-sea engineering, higher requirements are also put forward for the performance and function of titanium materials. The traditional design concept based on alloy element composition has been difficult to significantly improve the comprehensive performance of titanium alloys, thus limiting the application and development of titanium in the above-mentioned major national strategic fields. In response to this problem, researchers have found that introducing reinforcement phases into titanium alloys is an effective means to obtain both excellent mechanical properties and functions. The selection of reinforcement phases is the basis and key to determining its performance. Compared with traditional particle reinforcement phases such as TiC, TiN, and SiC, one-dimensional carbon nanotubes not only have physical properties such as high modulus, high strength, and excellent thermal and electrical conductivity, but also their special transfer load strengthening method can ensure that the mechanical properties are greatly improved without seriously damaging the plasticity and functional properties of the titanium alloy matrix. It is considered to be an ideal reinforcement phase for functional titanium alloys.
[0003] 3D printing is a digital modeling-based method that directly forms high-density complex parts by scanning the metal powder bed layer by layer. It has the advantages of high raw material utilization, short production cycle, and one-time forming of complex structures. It is very suitable for the near-net-shape manufacturing of titanium-based composite parts with difficult-to-process characteristics, and is expected to become an important production method for carbon nanotube-reinforced titanium-based composites. However, the lack of high-quality carbon nanotube-titanium alloy composite powder preparation technology restricts the development and application of titanium-based composite 3D printing technology. Mechanical mixing is currently the main technology for preparing carbon nanotube-titanium alloy composite powders. It has been used as a powder raw material for powder metallurgy carbon nanotube / titanium composites, but this powder cannot be used for 3D printing. The reasons are as follows: (1) The sphericity and fluidity of the powder are severely damaged, which impairs the powder spreading quality during the printing process; (2) The carbon nanotube structure is destroyed and cannot be retained after printing; (3) The carbon nanotubes are unevenly distributed, and the reinforcement effect is seriously degraded. At present, there is still a lack of high-quality composite powder materials that can be used for 3D printing of carbon nanotube-reinforced titanium-based composites. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-quality carbon nanotube-coated functional titanium alloy composite powder for 3D printing, so as to solve the problems of low sphericity, poor fluidity, carbon nanotube structural damage and uneven distribution, and impurity pollution introduced in the preparation of carbon nanotube-titanium composite powder by traditional mechanical mixing technology. The powder can be directly used as a powder raw material for 3D printing titanium-based composite materials, but its application is not limited to this, and can also be used in technical fields such as powder metallurgy, magnetron sputtering, and spraying.
[0005] In order to achieve the above object, the specific technical solution adopted by the present invention is as follows:
[0006] A method for preparing carbon nanotube-coated functional titanium alloy composite powder comprises the following steps:
[0007] (1) placing titanium alloy spherical powder into a fluidized bed reactor, connecting the gas control system, the fluidized bed reactor and the tail gas treatment device in sequence, checking the air tightness of the device, introducing inert gas to remove the air in the reactor, and placing the powder in a fluidized state;
[0008] (2) Removal of oxide film on the powder surface and activation of the internal alloy catalyst activity: high-purity inert gas is introduced into the fluidized bed reactor, the temperature of the working area inside the reactor is raised to the dissolution temperature of the oxide film on the surface of the titanium alloy, and the fluidized state of the powder inside the fluidized bed is maintained. The reaction time is 10 to 30 minutes;
[0009] (3) Catalytic chemical vapor deposition of carbon nanotubes: A mixture of inert gas, auxiliary gas, and carbon source gas is introduced according to a preset ratio, and the temperature is raised to the reaction temperature for catalytic chemical vapor deposition to induce in-situ deposition of carbon nanotubes on the surface of the titanium alloy powder for 5 to 120 minutes.
[0010] (4) After the reaction is completed, the introduction of the carbon source and the auxiliary gas is stopped and the flow rate of the inert gas is increased to maintain the fluidized state of the powder and stabilize for 5 to 10 minutes. The fluidized bed reactor is cooled to room temperature by air cooling, and the composite powder is taken out and sealed for storage.
[0011] The present invention uses spherical functional titanium alloy powder for 3D printing as a matrix, and uniformly coats the surface with carbon nanotubes, with a coating amount of 0.05 to 10.0 wt.%.
[0012] Preferably, the titanium alloy powder is a spherical powder for titanium alloy 3D printing with special functions such as hydrogen storage, shape memory, superelasticity, high damping, and high biocompatibility, such as a mixture of one or more of a hydrogen storage titanium alloy powder mainly composed of TiFe, a shape memory titanium alloy powder mainly composed of TiNi, and a biomedical titanium alloy powder mainly composed of TiCo, with a powder purity of ≥95% and a particle size distribution of 5 to 150 μm.
[0013] Preferably, the fluidized bed reactor in step (1) is a reaction device placed vertically to the ground and provided with a distribution plate inside. The gas can enter from the lower end or side end of the reactor, be discharged from the upper end and enter the exhaust gas treatment device. An electric furnace heating system is provided inside the fluidized bed reactor, and the reactor is made of heat-resistant metal materials such as stainless steel or tungsten-molybdenum alloy.
[0014] Preferably, the inert gas in step (1) is a gas that does not chemically react with the powder raw material, such as one or more of helium, neon and argon, with a purity higher than 99%.
[0015] Preferably, the time for introducing inert gas to remove air from the reactor in step (1) is 10-30 minutes.
[0016] Preferably, the dissolution temperature of the oxide film in step (2) is 450-650°C.
[0017] Preferably, the gas velocity of the inert gas in step (2) is 300 to 5000 sccm.
[0018] Preferably, the treatment time for removing the oxide film on the powder surface and activating the activity of the internal alloy catalyst in step (2) is 10 to 30 minutes.
[0019] Preferably, the gas capable of high temperature pyrolysis in step (3), such as one or more of methane, ethane, propane, ethylene, propylene, acetylene and propyne, has a purity higher than 99%.
[0020] Preferably, the auxiliary gas in step (3) is a gas that can regulate the chemical vapor deposition reaction rate and does not participate in the reaction, such as hydrogen, carbon dioxide, etc., and the purity is higher than 99%.
[0021] Preferably, the gas velocity of the mixed gas in step (3) is 300-5000 sccm, wherein the volume ratio of carbon source gas: auxiliary gas: inert gas is 1: (0-10): (1-100).
[0022] Preferably, in step (3), the reaction temperature is 450-850° C., and the deposition time is 5-120 min.
[0023] Preferably, after stopping the flow of the carbon source and the auxiliary gas in step (4), the flow rate of the inert gas is increased to the flow rate of the mixed gas.
[0024] Preferably, the composite powder in step (4) is a carbon nanotube-coated functional titanium alloy spherical composite powder, the mass fraction and aspect ratio of the carbon nanotubes in the composite powder increase with the extension of the reaction time, and the composition, thickness and structure of the coating layer also change with the change of the reaction time.
[0025] Preferably, the composite powder can be directly used as a powder raw material for 3D printing titanium-based composite materials, but its application is not limited to this, and it can also be used in technical fields such as powder metallurgy, magnetron sputtering, and spraying.
[0026] The composite powder of the present invention uses spherical alloy powder of titanium alloy with special functions as a matrix, and carbon nanotubes are evenly coated on the surface. It has high sphericity, good fluidity, low impurity content, and the carbon nanotubes are evenly distributed on the powder surface. The coating content can be accurately controlled in the range of 0.05-10.0wt.%.
[0027] The present invention constructs a coated composite powder with a core-shell structure, and uniformly introduces carbon nanotubes with high structural integrity on the basis of maintaining the high sphericity and fluidity of the original titanium alloy powder. Specifically, based on the high-temperature dissolution characteristics of the oxide film in the titanium alloy, the transition metal elements such as Fe, Ni, and Co in the functional titanium alloy powder are exposed through fluidized high-temperature treatment, and the catalytic properties of the above elements are activated by utilizing the high heat transfer and conduction characteristics of the fluidized bed, and carbon nanotubes are grown in situ on the powder surface through chemical vapor deposition. At the same time, the dynamic flow characteristics of the powder inside the fluidized bed can also ensure the uniform deposition of carbon nanotubes, avoid sintering and bonding between metal powders, and prepare coated carbon nanotube-titanium composite material powders that can be used for 3D printing, providing a raw material basis and technical guarantee for the development of high-performance, multifunctional titanium-based composite 3D printing technology.
[0028] Compared with the traditional method of preparing carbon nanotube-titanium composite powder by using carbon nanotube metal, the advantages of the present invention are:
[0029] The carbon nanotube-coated functional titanium alloy composite powder prepared by the present invention is a composite powder with a "core-shell structure" with good sphericity, good fluidity and low impurity content; the carbon nanotubes are evenly distributed and have strong bonding with the matrix; the carbon nanotubes have a complete structure and high purity; the aspect ratio, volume fraction, thickness and the like of the carbon nanotubes in the composite powder can be actively regulated by adjusting kinetic parameters such as carbon source concentration, reaction temperature and deposition time. The present invention dissolves the oxide film at high temperature and activates the catalytic activity of transition metal elements such as Ni, Co and Fe inside the powder, and in-situ grows carbon nanotubes on the surface of the functional titanium alloy in combination with fluidized bed chemical deposition. Compared with the traditional carbon nanotube-titanium composite powder preparation method, the present invention has the advantages of simple process, low cost, short process and easy large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the XPS spectrum analysis diagram of Ni 2p after the powder is treated by high-temperature fluidization;
[0031] Figure 2 This is a SEM image of the carbon nanotube-coated nickel-titanium spherical composite powder in Example 1 of the present invention;
[0032] Figure 3 This is a high-magnification SEM image of carbon nanotubes on the surface of the carbon nanotube-coated nickel-titanium spherical composite powder in Example 1 of the present invention;
[0033] Figure 4 This is a Raman spectrum distribution diagram of the carbon nanotube-coated nickel-titanium spherical composite powder in Example 1 of the present invention;
[0034] Figure 5 This is a SEM image of the carbon nanotube-coated nickel-titanium spherical composite powder in Example 2 of the present invention;
[0035] Figure 6 This is a high-magnification SEM image of carbon nanotubes on the surface of the carbon nanotube-coated nickel-titanium spherical composite powder in Example 2 of the present invention;
[0036] Figure 7 This is a SEM image of the carbon nanotube-coated cobalt-titanium spherical composite powder in Example 3 of the present invention;
[0037] Figure 8 This is a high-magnification SEM image of carbon nanotubes on the surface of the carbon nanotube-coated cobalt-titanium spherical composite powder in Example 3 of the present invention. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0039] Example 1
[0040] Weigh 100g of nickel-titanium spherical powder with a particle size of 15 to 53μm, add it to a fluidized bed reactor, introduce high-purity argon to remove the air in the system, and make the powder in a fluidized state. The gas velocity is 550sccm and the exhaust time is 10min. Raise the temperature of the working area inside the fluidized bed reactor to 550℃ and stabilize for 5min. Reduce the argon flow rate to 400sccm, introduce 50sccm of high-purity acetylene and 100sccm of high-purity hydrogen for chemical vapor deposition, and the reaction time is 45min. After the reaction is completed, stop introducing acetylene and hydrogen, increase the argon flow rate to 550sccm, and take out the fluidized bed reactor after stabilizing for 5min. Cool the fluidized bed reactor to room temperature, take out the powder, and sieve the composite powder with 200 and 500 mesh standard sieves to obtain carbon nanotube-coated nickel-titanium composite powder suitable for 3D printing.
[0041] Figure 1 This is the XPS spectrum analysis of Ni 2p after the powder was treated by high-temperature fluidization, indicating that after the treatment, the oxide film on the surface of the nickel-titanium alloy powder has dissolved into the matrix, and the internal Ni has been exposed and has catalytic activity;
[0042] Figure 2This is a SEM image of the carbon nanotube-coated nickel-titanium composite powder in Example 1. A large amount of carbon nanotubes are deposited on the surface of the powder, and the sphericity of the powder is not damaged;
[0043] Figure 3 This is a high magnification SEM image of carbon nanotubes on the surface of the composite powder in Example 1. The carbon nanotubes on the surface of the powder have the characteristics of high aspect ratio and complete structure;
[0044] Figure 4 : This is the Raman spectrum of the composite powder in Example 1. The characteristic peak intensity ratio of amorphous carbon to graphite is 0.76, indicating that the in-situ self-generated carbon nanotubes have high graphitization and crystallinity, further proving that the structural integrity is good.
[0045] Example 2
[0046] The difference between Example 2 and Example 1 is that ethylene is used instead of acetylene as the carbon source gas, the oxide film processing temperature is 650°C, carbon dioxide is selected as the auxiliary gas, and the deposition temperature is 850°C.
[0047] Figure 5 This is an SEM image of the carbon nanotube-coated nickel-titanium spherical composite powder in Example 4. The powder still maintains a high sphericity and the sediment phase is evenly distributed, indicating that ethylene is used as a carbon source gas and the oxide film dissolution temperature and deposition temperature are increased while still obtaining a uniformly coated nickel-titanium alloy composite powder of carbon nanotubes;
[0048] Figure 6 This is a high-magnification SEM image of the carbon nanotubes on the surface of the composite powder in Example 2. When ethylene is used as the carbon source gas, the number of carbon nanotubes on the powder surface is relatively small, the aspect ratio is reduced, and the content is reduced, indicating that high-quality carbon nanotubes uniformly coated with titanium alloy composite powders can still be obtained under the conditions of changing the carbon source selection and deposition temperature, but the change of the above conditions will significantly affect the growth behavior of the carbon nanotubes.
[0049] Example 3
[0050] The difference between Example 3 and Example 1 is that cobalt-titanium spherical powder is used as raw material instead of nickel-titanium spherical powder.
[0051] Figure 7 This is a SEM image of the cobalt-titanium spherical composite powder uniformly coated with carbon nanotubes in Example 3, indicating that the main component of the coating layer is carbon nanotubes, and the distribution is uniform, which confirms that the technical route of the present invention is also applicable to cobalt-titanium alloy powders, the catalytic activity of the internal cobalt element can be activated, and the carbon nanotubes can be deposited and grown in situ on the powder surface;
[0052] Figure 8This is a high-magnification SEM image of the carbon nanotubes on the surface of the composite powder in Example 3. The carbon nanotubes distributed on the powder surface have a high aspect ratio, a complete structure, and good quality, indicating that Co has a better catalytic effect than Ni.
[0053] The carbon nanotube-coated functional titanium alloy spherical composite powder of the present invention has carbon nanotubes uniformly coated on the surface and has the advantages of high sphericity, good fluidity, low impurity content, uniform distribution of carbon nanotubes on the powder surface, and accurate control of the carbon nanotube coating amount.
[0054] The process parameters (such as temperature, time, etc.) of the present invention can realize the method by taking upper and lower limits and interval values, and the embodiments are not listed one by one here.
[0055] Any contents not described in detail in the present invention can be based on the conventional technical knowledge in the art.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon nanotube-coated functional titanium alloy composite powder, the preparation method comprising the following steps: (1) placing functional titanium alloy powder into a fluidized bed reactor, introducing inert gas to remove air from the reactor, and placing the powder in a fluidized state; (2) introducing high-purity inert gas into the fluidized bed reactor, raising the temperature of the working area inside the reactor to the dissolution temperature of the oxide film on the surface of the functional titanium alloy powder to remove the oxide film on the powder surface and activate the activity of the alloy catalyst inside the powder, maintaining the fluidized state of the powder inside the fluidized bed, and the reaction time is 10 to 30 minutes; (3) introducing a mixed gas of an inert gas, an auxiliary gas, and a carbon source gas according to a preset ratio to perform catalytic chemical vapor deposition to induce in-situ deposition of carbon nanotubes on the surface of the titanium alloy powder for a period of 5 to 120 minutes; (4) After the reaction is completed, the carbon source and auxiliary gas are stopped and the inert gas flow rate is increased to maintain the fluidized state of the powder. The fluidized bed reactor is cooled to room temperature by air cooling, and the composite powder is taken out and sealed for storage.
2. The preparation method according to claim 1, characterized in that: The functional titanium alloy powder is a mixture of one or more of TiFe alloy powder, TiNi alloy powder and TiCo alloy powder, with a powder purity of ≥95% and a particle size distribution of 5 to 150 μm.
3. The preparation method according to claim 1, characterized in that: The inert gas is one or more of helium, neon and argon.
4. The preparation method according to claim 1, characterized in that: The dissolution temperature of the oxide film on the surface of the functional titanium alloy powder is 450-650°C.
5. The preparation method according to claim 1, characterized in that: The carbon source gas is one or more of methane, ethane, propane, ethylene, propylene, acetylene and propyne.
6. The preparation method according to claim 1, characterized in that: The auxiliary gas is hydrogen and / or carbon dioxide.
7. The preparation method according to claim 1, characterized in that: The total gas velocity of the mixed gas is 300-5000 sccm, wherein the volume ratio of the carbon source gas: the auxiliary gas: the inert gas is 1: (0-10): (1-100).
8. The preparation method according to claim 1, characterized in that: The reaction temperature of the catalytic chemical vapor deposition is 450-850°C.
9. The preparation method according to claim 1, characterized in that: The surface of the composite powder is uniformly coated with carbon nanotubes, and the coating amount of the carbon nanotubes is 0.05-10.0wt.%.
Citation Information
Cited By
Carbon nanomaterial reinforced metal matrix composite component and manufacturing method thereof
CN122274217A